Quantum dynamics for classical systems with applications of the number operator - Bagarello, Fabio, 1964- (Wiley, 2013)
"With a focus on the relationship between quantum mechanics and social science, this book introduces the main ideas of number operators while avoiding excessive technicalities that aren't necessary in understanding the various mathematical applications. It discusses the use of mathematical tools related to quantum mechanics and features applications in finance, biology, and social science; systematically shows how to use creation and annihilation operators for classical problems; and addresses the recent increase in research and literature on the many applications of quantum tools in applied mathematics"--